2022
DOI: 10.1111/eva.13432
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of hybridization in wild boar populations reveals adaptive introgression from domestic pig

Abstract: The admixture of domestic pig into French wild boar populations has been monitored since the 1980s thanks to the existence of a cytogenetic difference between the two sub-species. The number of chromosomes is 2n = 36 in wild boar and 2n = 38 in pig, respectively. This difference makes it possible to assign the "hybrid" status to wild boar individuals controlled with 37 or 38 chromosomes. However, it does not make it possible to determine the timing of the hybridization(s), nor to guarantee the absence of domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…In addition to the benefits of having high Ne , hybridization is known to introduce novel adaptive variations and further increase fitness (Adavoudi & Pilot, 2022 ). In fact, hybridization in French wild boar revealed adaptive introgression from domestic pigs (Mary et al., 2022 ). Our study suggests that a high Ne in native pigs can be achieved by hybridization with wild pigs, thus necessitating the comanagement of PhNPs and Philippine wild pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the benefits of having high Ne , hybridization is known to introduce novel adaptive variations and further increase fitness (Adavoudi & Pilot, 2022 ). In fact, hybridization in French wild boar revealed adaptive introgression from domestic pigs (Mary et al., 2022 ). Our study suggests that a high Ne in native pigs can be achieved by hybridization with wild pigs, thus necessitating the comanagement of PhNPs and Philippine wild pigs.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly likely that domestic pigs sporadically crossed with wild boars [ 10 ]. The frequent hybridisation of these two breeds was found in the studies on the European population [ 10 , 11 , 12 , 13 ]. Studies of the MC1R (melanocortin 1 receptor) gene in the Polish population of wild boars also proved the existence of admixed genotypes [ 14 , 15 ].…”
Section: Pig and Wild Boar Phylogeneticsmentioning
confidence: 99%
“…As pigs and wild boars are closely related, and genetic introgression from domestic pigs into European wild boar has been proved [ 74 , 76 ], phylogenetically close taxa distinguishing requires introduction of high-throughput, SNP-based (SNP, Single Nucleotide Polymorphism) molecular techniques. A 70K SNP chip was used in a French study [ 13 ] to determine the timing of the hybridisation (s) and to check the domestic pig admixture in the wild boar population. The study revealed that among wild boars, 83% to 100% of animals had a genome of “wild” origin and local ancestry analyses showed adaptive introgression from a domestic pig.…”
Section: Genetic Markers Used For Pig and Wild-boar Distinguishingmentioning
confidence: 99%
“…Gene flows between domesticated species and their wild relatives have been identified in several studies in animals [ 1 3 ] and plant species [ 4 , 5 ]. This phenomenon is noted when cultivated genomic variants occur in unmanaged naturally occurring populations in natural environments.…”
Section: | Introductionmentioning
confidence: 99%